Natural Gas Decarbonization as Tool for Greenhouse Gases Emission Control - Abánades, Alberto (Frontiers in Energy Research, 2018)
The reduction and control of carbon dioxide emissions of the energy system and other industrial processes using fossil resources is one of the main concerns of our society. Natural gas may contribute to reduce such emissions as it is the fossil with the highest H/C ratio. In addition, a deep reduction of emissions will require the development of technologies as carbon capture and sequestration (CCS) or utilization (CCU), or direct fossil decarbonization. Some practical approaches integrated in the Power-to-Gas scheme to the application of natural gas decarbonization are presented. The introduction of this technology in hydrogen mobility seems to be viable, providing a carbon-free production on site without hydrogen or carbon dioxide transport and storage. The integration of direct decarbonization into combined cycle plants for centralized electricity production is justified for carbon penalties above 50 €/kg.